Do Experiences with Medicare Managed Care Vary According to the Proportion of Same‐Race/Ethnicity/Language Individuals Enrolled in One's Contract?. (9th March 2015) - Price, Rebecca Anhang; Haviland, Amelia M.; Hambarsoomian, Katrin; Dembosky, Jacob W.; Gaillot, Sarah; Weech‐Maldonado, Robert; Williams, Malcolm V.; Elliott, Marc N.
<x xml:space="preserve">Abstract</x> Objective To examine whether care experiences and immunization for racial/ethnic/language minority Medicare beneficiaries vary with the proportion of same‐group beneficiaries in Medicare Advantage (MA) contracts. Data Sources/Study Setting Exactly 492, 495 Medicare beneficiaries responding to the 2008–2009 MA Consumer Assessment of Healthcare Providers and Systems (CAHPS) Survey. Data Collection/Extraction Methods Mixed‐effect regression models predicted eight CAHPS patient experience measures from self‐reported race/ethnicity/language preference at individual and contract levels, beneficiary‐level case‐mix adjustors, along with contract and geographic random effects. Principal Findings As a contract's proportion of a given minority group increased, overall and non‐Hispanic, white patient experiences were poorer on average; for the minority group in question, however, high‐minority plans may score as well as low‐minority plans. Spanish‐preferring Hispanic beneficiaries also experience smaller disparities relative to non‐Hispanic whites in plans with higher Spanish‐preferring proportions. Conclusions The tendency for high‐minority contracts to provide less positive patient experiences for others in the contract, but similar or even more positive patient experiences for concentrated minority group beneficiaries, may reflect cultural competency, particularly language services, that partially or fully counterbalance the poorer overall quality of these contracts. For some beneficiaries, experiences may be just as positive in some high‐minority plans with low overall scores as in plans with higher overall scores.